THE EFFECT OF SEEDING RATES ON FIELD GERMINATION AND GROWTH–DEVELOPMENT OF SEEDS OF THE NEW “SHUKRONA” VARIETY OF AUTUMN SOFT WHEAT - G‘ulomjon Oqbutaevich Uzaqov, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article describes the optimal seeding rate for growing the new local winter soft wheat variety "Shukrona" in the southern region of the republic. It is noted that in the light gray soils of the Kashkadarya region, the field germination of seeds of the newly developed winter soft wheat variety "Shukrona" is directly proportional to the seeding rate. Although no difference in the duration of seed germination was observed when the "Shukrona" variety was sown at the optimal time, field germination varied between 82 and 88 percent depending on the seeding rate. The growing season of the "Shukrona" variety was found to vary from 224 to 228 days depending on the seeding rate, with the longest growing season observed when planting 4.0 million seeds per hectare.